Phytochemical Screening and Determination of Phenolic and Flavonoid Contents in Ethanol Extract of Phyllanthus emblica L. Fruit - Syahputra, Hafid (Indonesian Journal of Pharmaceutical and Clinical Research, 2024)
Phyllanthus emblica L. fruit is known for its potent antioxidant activity, closely associated with its phenolic and flavonoid content. This study aims to analyse the secondary metabolite composition and determine the total phenol and flavonoid levels in Phyllanthus emblica fruit. The extraction process was carried out using the maceration method with 96% ethanol as the solvent, followed by a rotary evaporator evaporation. The ethanol extract was subjected to phytochemical screening with colour reagents, and the total phenol and flavonoid contents were assessed using a colourimetric method. TheFolin–Ciocalteu reagent was employed for complex phenolic compounds, with gallic acid as the standard reference. The total flavonoid content was determined using the aluminium chloride method, with quercetin as the standard. The results indicated that the ethanol extract of Phyllanthus emblica fruit contained alkaloids, saponins, flavonoids, tannins, triterpenoids, and glycosides. The study found that the total phenol content was 61.1271±3.86 mg GAE/g extract, while the total flavonoid content was 3.3742±0.06 mg QE/g extract.